Investing in the development of the next generation of MCH leaders - McDonnell, Karen A.; Percy, Jamal; Anders, Lisa; Brown, Monique J.; Richman, Alice R.; Deardorff, Julianna; Ruiz, Monica S.; Liu, Jihong; Russell, Kelli; Snyder, Audrey; Marshall, Cassondra (Frontiers in Public Health, 2025)
The public health landscape is constantly evolving to address the strengths and needs of the community. Training for the public health workforce is leading the way, establishing an ecosystem approach that integrates individuals within social, political, and environmental contexts to promote health equity within a framework of social justice. One area of public health that is innovatively preparing the next generation of leaders is maternal and child health (MCH). In the United States, key indicators of health disparities within MCH remain stagnant, highlighting the need for training programs that develop future MCH professionals from diverse backgrounds. These professionals will deliver culturally and linguistically appropriate services for an increasingly underserved and underrepresented population, both in the US and around the world. The MCH Leadership, Education, and Advancement in Undergraduate Pathways (LEAP) training program provides coordinated opportunities for undergraduate students, faculty, agencies, organizations, and communities to work together for developing the future MCH public health workforce. Effective and respectful leadership development in MCH requires investment in fundamental educational, research, and community-engaged practice-based skill sets cultivated in undergraduate programs. Currently, six funded programs in the MCH LEAP portfolio share a collective mission to train undergraduates who have historically had a minimal presence to become MCH leaders of tomorrow. These programs also make changes to organizational structures that reflect the geographic and demographic representation of their communities. Mixed-methods evaluations, encompassing both qualitative and quantitative approaches, illustrate the MCH LEAP training program’s effectiveness in introducing and developing the competencies for the next generation of the MCH workforce.